PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL)UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 007 PEMATANG IBUL KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Asmaita, Asmaita; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the fact that IPS students' learning outcomes are low and did not reached of the KKM. There were 26 students who took the set of the test. Which 16 students who not reach the KKM (16,53%) and those who reachedthe KKM only 10 students (38,46%).this research is a classroom action research conducted on students of grade V IPS SDN 007 Pematang Ibul,Bangko Pusako Rokan Hilir.the research indtrument consisti of learning tools based on the educational level curuculum (KTSP)or known as the 2006 curiculum, such as Syilabus,RPP, students worksheet, and observation Sheet, this research was conducted by to cycles, each cycles consists of three meeting face –to face meeting twice, and one daily test at the end of the cycles, with using the learning model of CTL, will improve student learning outcome, this can be seen at the first meeting of the cycles one in teacher and student activities. In the first meeting the teacher activities score get 10 (62,5%) with categorized poor to average. In the second meeting, the score is 12 (75%) with categorized average to good. In the second cycles of the first meeting the teacher activities score get 13 (81,25%) with categorized good to excellent and at the second meeting the score is 15 (93,75%), it categorized good to excellent. In student activities at the first cycleson the first meeting, the score is 10 (62,5%) with categorized poor to averageat the second meeting the score is 10 (62,5%) with categorized poor average. Then, in the first meeting on the second cycles. The student get score 11 (68,75%) with categorized poor to average and on the second meeting the score is 14 (87,5%) categorized goog to excellent. Based on the data abone only 10 student (38,46%) can reached the KKM. After cycle on the were given about 18 students reached the KKM, it becomer 18 students (69,23%). At the second cycle, were increased about 24 students (92,30%). Therefore the average value obtained by the students classically is only (38,46%) at the first cycle were increased up to (92,30%). It means that the classical value obtained by the students has been above of the KKM.Keywords: CTL Learning Model of CTL, Learning OutcomesIPS